2020
DOI: 10.1108/bfj-05-2019-0363
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value, trust and purchase intention of organic food: a study with Brazilian consumers

Abstract: PurposeThe consumption of organic food grows worldwide, increasing the need of studies seeking to understand factors influencing its consumption. To extend the understanding of organic food market, the present research seeks to explore the effect of perceived value on consumer trust and purchase intention in Brazil.Design/methodology/approachA survey with 274 Brazilian consumers of organic food was carried out. Perceived value was measured through four dimensions: functional, economic, social and emotional. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(191 citation statements)
references
References 56 publications
9
107
1
34
Order By: Relevance
“…Despite the early and expanding context of Brazil's organic food market, certification remains the core factor in enhancing and improving trust among consumers (Aitken et al, 2020;Janssen and Hamm, 2014;Liang, 2016). Moreover, the organic certification can affect consumer's attitude (Lee et al, 2020) and be a decisive determinant to purchase this kind of food, using factors such as certification to recognize and ensure the veracity of the information provided (Teng and Wang, 2015;Watanabe et al, 2020). Besides, the organic label can also impact consumers' perception about organic food (Nadricka et al, 2020).…”
Section: Consumer Trust and Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the early and expanding context of Brazil's organic food market, certification remains the core factor in enhancing and improving trust among consumers (Aitken et al, 2020;Janssen and Hamm, 2014;Liang, 2016). Moreover, the organic certification can affect consumer's attitude (Lee et al, 2020) and be a decisive determinant to purchase this kind of food, using factors such as certification to recognize and ensure the veracity of the information provided (Teng and Wang, 2015;Watanabe et al, 2020). Besides, the organic label can also impact consumers' perception about organic food (Nadricka et al, 2020).…”
Section: Consumer Trust and Purchase Intentionmentioning
confidence: 99%
“…However, it does not disclose aspects assigned to certification labels in economically emerging countries like Brazil. The identified Brazilian studies (1) explore the process of adopting organic labels by small farmers (Blanc and Kledal, 2012); (2) describe the process of institutionalization of federal regulations regarding organic systems, including certification labels (Cadiotto, 2018) and (3) demonstrate that trust in certification labels is predicted by functional and emotional values (Watanabe et al, 2020). Other studies address genetically modified food (Hakim et al, 2020) and warning labels in food products (Khandour et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are becoming increasingly concerned about the environment, and their purchasing behaviour often reflects their sensitivity to ecological matters (Koo et al , 2015; Ghali, 2020). The recent desire to purchase and consume organically produced food has altered many people's buying patterns (Scuderi et al , 2019; Mohammed et al , 2020; Watanabe et al , 2020). Over the last 20 years in particular there has been an exponential rise, with this sector growing much faster than traditional foodstuffs (Cushman and Wakefield, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that trustworthiness positively affects purchase intention (β = 0.427; p <0.001), thereby confirming H5. Many studies in the literature generally address the effect of trustworthiness on purchase intention (Lin and Lu, 2010;Watanabe et al, 2020;Kuşcu, Durmaz, and Sazkaya, 2019;Semuel and Chandra, 2014). Tong and Su (2018) found that consumer trust has a positive effect on purchase intention.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that many studies address the effect of trust on purchase intention in general (Lin and Lu, 2010;Watanabe et al, 2020;Kuşcu et al, 2019;Semuel and Chandra, 2014). In turn, Tong and Su (2018) studied young American consumers of organic clothing products.…”
mentioning
confidence: 99%